Elementos de Manipulação e Fraude Eleitoral Detetados nas Eleições Angolanas de 2022 - David Boio (Cadernos de Estudos Africanos)
During the 2022 Angolan elections, the incumbent engaged in practices that undermined electoral rules, causing multiple attacks on electoral integrity. The fraudulent practices occur well in advance of elections and consist of three stages, as identified in the relevant literature. Firstly, the pre-election period is marked by modifications to the regulations. Secondly, during the electoral campaign, the key features are electoral violence, voter bribery, and heightened media control. Finally, the post-election period illustrates bias within the bodies responsible for electoral litigation. Elections conducted in authoritarian regimes, like that of Angola, result in no more than a democratic simulacrum, as they violate the minimum requirements of a democratic election.